Additively Manufactured Absorbable Porous Metal Implants – Processing, Alloying and Corrosion Behavior - Jahr, Holger; Li, Yageng; Zhou, Jie; Zadpoor, Amir A.; Schröder, Kai-Uwe (Frontiers in Materials, 2021)
Treating large bone defects is still a clinical challenge without perfect solution, mainly due to the unavailability of suitable bone implants. Additively manufactured (AM) absorbable porous metals provide unparalleled opportunities to realize the challenging requirements for bone-mimetic implants. Firstly, multi-scale geometries of such implants can be customized to mimic the micro-architecture and mechanical properties of human bone. The interconnected porous structure additionally increases the surface area to facilitate adhesion and proliferation of bone cells. Finally, their absorption properties are tunable to maintain the structural integrity of the implant throughout the bone healing process, ensuring sufficient loadbearing when needed and full disintegration after their job is done. Such a combination of properties paves the way for complete bone regeneration and remodeling. It is important to thoroughly characterize the biodegradation behavior, mechanical properties, and bone regeneration ability when developing ideal porous absorbable metal implants. We review the state-of-the-art of absorbable porous metals manufactured by selective laser melting (SLM), with a focus on geometrical design, material type, processing, and post-treatment. The impact of the latter aspects on absorption behavior, resulting mechanical properties, and cytocompatibility will also be briefly discussed. In comparison to their solid inert counterparts, AM absorbable porous metals (APMs) have shown many unique properties and hold tremendous potential to further optimize their application-specific performance due to their flexible geometrical design. We further highlight challenges in adopting AM APMs for future Orthopedic solutions.